(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2021)
The aim of this study was to develop and evaluate nutritional quality of weaning food from indigenous sources. Three types of weaning food named as F-1 (wheat flour, soya flour, rice flour), F-2 (wheat flour, soya flour, malt extract) and F-3 (malted wheat flour, soya flour, peanuts, lentils, and carrots powder) were prepared for the study. Nutritional quality, functional and sensory characteristics of the developed food were investigated. Functional property as water absorption capacity, bulk density, water binding capacity, solubility, swelling power and viscosity varied from 136.24-145.83 (g/100g), 0.57-0.75 (g/cm3), 410.54-471.07 (g/100g), 35.05-48.81%, 6.16-11.79%, 33.48-39.41 (mp/s), respectively. Essential amino acids content of F-3 such as threonine, alanine, valine, methionine, isoleucine, leucine, histidine and lysine were 0.77, 0.67, 0.45, 0.47, 0.51, 0.62, 0.41 and 1.73 (g/100g), respectively. Compositional analysis of fatty acid indicates that it contains 16.01% palmitic acid, 4.27% stearic acid, 45.90% linoleic acid and 25.55% oleic acid in F-3. Bangladesh J. Sci. Ind. Res.56(1), 29-38, 2021